WORKING CAPITAL MANAGEMENT STRATEGIES OF NIGERIAN MANUFACTURING FIRMS AND THE EFFECTS ON CORPORATE PERFORMANCE - Edomobi, Nonye; Ebiringa (Prof), Ofoegbulam Thaddeus; Chris-Ejiogu, Uzoamaka Gloria (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
The study examined the working capital management strategies of Nigerian Manufacturing Firms and effect on Corporate Performance. Working capital management was decomposed into five variables being account receivable management (ARM), account payable management (APM), inventory management (INVM), cash conversion cycle (CCC) and cash conversion efficiency (CCE) which serve as the explanatory variables of the study while Corporate Performance was proxied by Return on Assets (ROA). The data for the study were collected from the Financial Statement and Annual Accounts of the selected firms covering a data panel framework of 20 years period (2000 to 2020) and nine (9) firms specifically were selected. The analysis was based on the ARDL regression technique was used to estimate the regression model while the probability values of the ARDL regression estimates were used to test the hypotheses at 0.05 level of significance. The result showed that: Account receivable management strategy have long run and no short run effect on return on asset of quoted manufacturing firms in Nigeria; Account payable  management strategy have long run and no short run effect on return on asset of quoted manufacturing firms in Nigeria; Inventory management strategy have long and short run effect on return on asset of quoted manufacturing firms in Nigeria; Cash conversion cycle strategy have long and short run effect on return on asset of quoted manufacturing firms in Nigeria; and Cash conversion efficiency strategy have no long and short run effect on return on asset of quoted manufacturing firms in Nigeria. Further analysis revealed that account receivable, account payable inventory management and cash conversion efficiency had causal effects on return on assets. However, there is no causal relationship between cash conversion cycle strategy and return on asset of quoted manufacturing firms in Nigeria. The study thus concluded that working capital management strategies have significant effect on the financial performance of firms, and that the degree of effect differs by period, type of strategy and financial performance indicator. It was recommended among others that management of firms should firms increase the supplies to customers and allow credit to its customers, and firms should also explore the use of short-term credit in financing their business. The study contributed to knowledge by employing long run panel technique in investigating the working capital and firm performance nexus in Nigeria.